2011
DOI: 10.4236/ijcm.2011.25092
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Carotid Plaque, Intima Media Thickness (IMT), Resistivity Index (RI) and Pulsatility Index(PI) in Asian-Indian Patients with Acute Ischemic Stroke with and without Type2 DM

Abstract: Aim: To determine the relationship of carotid plaque, intima media thickness (IMT), resistivity index (RI) and pulsatility index (PI) and prevalence of different risk factors with acute ischemic stroke and stroke subtypes in both diabetic and non-diabetic subjects. Materials and methods: 80 cases of acute ischemic strokes and 40 healthy controls were included in the study. The plaque, IMT, RI and PI were measured by carotid duplex ultrasound. Results: 31 subjects were Type 2 diabetic, 54 hypertensive while 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…showed the prevalence of DM was 38.7% among stroke patients [22]. Similar observation was reported by Nagaraja D et al from Bangalore i.e.…”
Section: Discussionsupporting
confidence: 78%
“…showed the prevalence of DM was 38.7% among stroke patients [22]. Similar observation was reported by Nagaraja D et al from Bangalore i.e.…”
Section: Discussionsupporting
confidence: 78%
“…[12] Present study also showed higher CIMT with multiple co morbidities and the difference was statistically significant. Similar findings were noted in Sahoo et al [8] Study done by Das et al [13] on Asian Indian stroke cases showed a higher IMT among diabetic stroke patients, but the study had lesser number of cases of ischemic stroke with age-matched controls. Similarly in the present study, the CIMT was significantly higher among hypertensive, smokers, and obese patients.…”
Section: Resultsupporting
confidence: 87%
“…In the present study showed that 31 cases (62%) had PACS, 7 (14%) TACS, 7 (14%) LACS, 5 (10%) POCS, which was consistent with a similar study found PACS 40%, LACS 28.75%, TACS 15% and POCS 10% 16 . On multivariate analysis by using ANOVA test, mean IMT more markedly found in the LACS, PACS AND POCS category which was not statistically significant (P > 0.05), but a previous study found that mean IMT was more in POCS and TACS category 6 . Plaque was associated with TACS category (P 0.000) and in our study more plaque (24 out of 42) was associated with PACS category (P > 0.05).…”
Section: Discussionmentioning
confidence: 58%
“…The CIMT is a marker generalized atherosclerosis, and provides a noninvasive method for the risk assessment of stroke 4 . In the ARIC study (The atherosclerosis risk in community) -increased CIMT may be used as a predictive tool for predicting the future ischemic stroke and as a monitoring tool in lipid lowering medication 5,6 .…”
Section: It Is Thought To Be An Indicator Of Atherosclerosismentioning
confidence: 99%